Affirmation of passenger traffic flows on the Danube corridor : perspective of river cruise tourism - Poletan-Jugović, Tanja (Array, 2020)
Cruise tourism as a propulsive branch of tourism is being increasingly affirmed in the field of river transport. Accordingly, the main research problem in this paper is the analysis of the possibility of further affirmation and growth of passenger flows on river cruises on the Danube as the backbone of river traffic in the European Union. In the context of the defined research problem, the paper analyzes: relevant geo–traffic and socio–economic characteristics of the Danube, relevant indicators of passenger flows on cruises on the Danube – intensity, structure, dynamics and distribution of passenger traffic flows. Based on the aforementioned content, the further dynamics of passenger flows on cruises is concluded and forecasted, and the guidelines and factors of valorization of cruise tourism along the Danube Corridor are highlighted.